Skincare Education Analysis on TikTok Account @dokterdetektif - Cindy Prastia Putri; Aulia Rahma wati; Ririn Puspita Tutiasri (Universitas Muhammadiyah Ponorogo, 2026)
The development of social media has changed people's communication patterns, including in obtaining health and beauty information. TikTok, as a short video-based platform, is now used not only for entertainment but also as an educational medium by professionals, including doctors. One prominent account in providing skincare education is @dokterdetektif. This account is widely known for presenting information based on scientific data and laboratory test results related to various skincare products. This study aims to analyze the educational content on the @dokterdetektif TikTok account with a focus on how the content is structured, packaged, and delivered to the audience. The approach used in this study is a qualitative approach with the content analysis method according to Klaus Krippendorff. The analysis stages include unitizing, sampling, recording, reducing, inferring, and narrating. Data were obtained from 82 video content uploaded by the @dokterdetektif account between September 2024 and May 2025. The results show that the educational content on this account is divided into five main categories: scientific product education, reactions to viral products, information on the dangers of illegal products, skincare content literacy, and educational interactions. The content is delivered with a systematic, data-driven approach, yet remains light and entertaining. The use of casual language and interaction with the audience make the educational message more easily accepted. Furthermore, the credibility of the source as a doctor strengthens the audience's trust in the information conveyed. This study concludes that the TikTok account @dokterdetektif has successfully utilized social media optimally as a means of public education about skincare, while also demonstrating that doctors as influencers can play an active role in public health literacy. This research is expected to serve as a reference in the development of health education content in digital media, as well as provide academic contributions to the study of digital communication. Keywords: TikTok; Skincare Education; Content Analysis; Social Media; Influencer Doctors;